Transition to advanced market economies * Plenary lectures - Straszak, Andrzej (1931– ); Stefanski, Jacek; Owsinski, Jan (Instytut Badań Systemowych. Polska Akademia Nauk, 1992)
Christopher Clague, Maurice Shutler, Jan Węglarz, J.P. Brans
23-28 stron ; 21 cm
Bibliografia s. --0